1979
DOI: 10.1111/j.1399-3054.1979.tb02633.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glyphosate on Metabolism of Phenolic Compounds

Abstract: Amounts of extractable phenylalanine ammonia-lyase (PAL; E.C. 4.3.1.5) activity increased in the axes of 3-day-old, dark-grown soybean seedlings IGlyeine max (L.) Merr.] shortly after the seedlings were transferred to glyphosate IAf-(phosphonomethyl)-glychie] solutions. The stimulation of PAL activity in herbicide-treated tissue (as compared to control tissue) was detectable as early as 12 h after treatment, whereas growth inhibition (length, fresh weight and dry weight) was not significantly affected until 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
72
3
2

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 27 publications
4
72
3
2
Order By: Relevance
“…However, as a secondary effect, there is an inhibition in the synthesis of phenolic compounds deriving from those amino acids, which increases the activity of the PAL (phenylalamine ammonia lyase) enzyme due to a response effect (Duke & Hoagland, 1985). The PAL acts in the lyase of phenylalanine and tyrosine amino acids, resulting in the formation of phenolic acids and NH 4 + (Hoagland et al, 1979). The glufosinate ammonium herbicide inhibits the action of the glutamine sinthetase, which is responsible for the glutamate synthesis from ammonium and glutamine.…”
Section: Effect Of Herbicidesmentioning
confidence: 99%
“…However, as a secondary effect, there is an inhibition in the synthesis of phenolic compounds deriving from those amino acids, which increases the activity of the PAL (phenylalamine ammonia lyase) enzyme due to a response effect (Duke & Hoagland, 1985). The PAL acts in the lyase of phenylalanine and tyrosine amino acids, resulting in the formation of phenolic acids and NH 4 + (Hoagland et al, 1979). The glufosinate ammonium herbicide inhibits the action of the glutamine sinthetase, which is responsible for the glutamate synthesis from ammonium and glutamine.…”
Section: Effect Of Herbicidesmentioning
confidence: 99%
“…To date, the only nonmicrobial studies relating enzyme data to glyphosate effects were those (9)(10)(11)17), testing a hypothesis that glyphosate-mediated induction of PAL in higher plants might account for growth inhibition. However, it now seems likely that PAL induction is an effect, rather than the cause, of metabolic events initiated by glyphosate (1).…”
mentioning
confidence: 99%
“…Gresshoff (12) reported reversal of glyphosate inhibition of Arabidopsis thaliana seedlings with a combination of phenylalanine and tyrosine. In contrast, Duke and Hoagland (6) observed increased inhibition by glyphosate of corn seedling growth when phenylanine and tyrosine were added.Several studies (7,8,16) show that glyphosate treatment can decrease free phenylalanine and tyrosine levels. Recent studies have indicated that glyphosate inhibits the synthesis of flavonoids and chlorogenic acid in buckwheat hypocotyls (17) and causes an accumulation of shikimate that is significantly correlated with a…”
mentioning
confidence: 99%